Pengaruh Sikap dan Persepsi Kontrol Perilaku Terhadap Niat Whistleblowing Internal-Eksternal dengan Persepsi Dukungan Organisasi Sebagai Variabel Pemoderasi - Ilham Maulana Saud (Journal of Accounting and Investment, 2016)
This study aims to examine the influence of attitude and perceived behavior control empirically toward the whistleblowing intention of the internal-external with the perceived organizational support as the moderating variables. This study using survey method with 127 respondents of the permanent staffs of Universitas Muhammadiyah Yogyakarta (UMY) and employs hierarchical regression analysis. The results reveal the attitude has significant influence toward internal whistleblowing intention and the perceived of organizational supporting has significant influence as moderating variable which strengthen the influence of the perceived behavior control toward the internal-external whistleblowing intention.